An introduction to the reception and adaptation of the romantic aesthetic in the nineteenth-century Ecuador: the influence of Herder and the romantic aesthetic of the sublime in the literature and landscape painting - Puig Peñalosa, Xavier (Estudios de Filosofía, 2015)
New romantic proposals made above all by numerous travelers (scientists, explorers, artists, technicians, businessmen, etc.) who arrived to Ecuador -mainly from the first third of the 19th century- through text (theoretical or literary subsequently some translated to the Spanish), films, photographs, etc., accounted for a gradual change in the existing neoclassical esthetic-artistic taste. At the time, there was a syncretic adaptation among those postulates and the local idiosyncrasies (customs, beliefs, traditions, forms life, etc.) that found its greatest specificity in the ideas of Herder and in part, its implementation of the themes of nature and, more particularly, in the plastic and literary representation of the romantic native landscape from the aesthetic categories of the sublime. Likewise, these forms of representation would symbolically affirm and build the unitary project of nation (in Ecuador). Therefore, and from that standpoint, its impact mainly in the fields of painting and literature will be addressed in this essay.